TINDAK PIDANA KORUPSI DIREKSI PERSEROAN BUMN YANG MENIMBULKAN KERUGIAN KEUANGAN NEGARA - Henry Donald Lumban Toruan (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Determination of Directors of state-owned company as perpetrators of corruption that cause financial loss to the state being debated. Actions in the framework of the management of the company's Board of Directors conduct business relationships with other companies is intended pursuit for profit purposes set forth in the articles of association of the company. If the state-owned company suffered losses in the business relationship, then it becomes a loss to the state even after careful and responsible as set out in the Company Law. Unfortunately the state losses at state- owned company made an unlawful act of corruption in the Corruption Eradication Act (Act PTPK). Establishes the Board of Directors as a subject perpetrators of corruption in PTPK Law, caused the expansion of the formulation of the notion of public servants, not just civil servants who are subject to the Civil Service Act but also includes those who receive salaries and wages of state finance or state facilities. In terms of state-owned company is a legal entity which has the property that is separate from its shareholders. When capital from state financial aid is included in the state-owned company in the form of capital stock, the capital instantly become the company's wealth. If any damage occurs as a result of the company's business relationships, then it becomes a loss company. Shareholders are only responsible for the loss of shares owned by the company. Kata kunci: Kerugian perseroan BUMN bukan kerugian keuangan Negara